Clinical study of a chest‐based cuffless blood pressure monitoring system. Issue 5 (2nd June 2020) - Heydari, Fatemeh; P. Ebrahim, Malikeh; Redoute, Jean‐Michel; Joe, Keith; Walker, Katie; Avolio, Alberto; R. Yuce, Mehmet
Abstract: This work presents a clinical study of a chest‐based blood pressure (BP) monitoring technique. This research was designed to examine pulse transit time (PTT) and to measure beat‐to‐beat and cuff‐based systolic BP (SBP) and diastolic BP (DBP). The PTT values were extracted as the time difference between the end of the pre‐ejection period (PEP) measured using an on‐body continuous‐wave radar (CWR) sensor and the pulse arrival time (PAT) in central arteries extracted from the shoulders' bio‐impedance (BImp) signal. The system was investigated under three experimental conditions: (a) resting at various postures; (b) rising exercise stress, followed by resting; and (c) spraying inconstant doses of glyceryl trinitrate (GTN) medicine and recovery. Data were collected from 43 volunteers who participated in posture recordings, 26 undertook exercises and 17 experienced GTN spray. The BImp‐based PTT was compared with PPG‐based one (peripheral) in terms of BP estimation. Various mathematical methods of calculating BPs from PTTs were investigated to gain the most accurate outcomes. We demonstrate the accuracy of each model in this work. Our study found that cuffless BP determined from PTT derived from central arteries shows more than 3% accuracy compared to that determined from peripheral arteries.